Role of calcium overload-mediated disruption of mitochondrial dynamics in offspring neurotoxicity due to methylmercury exposure during pregnancy and lactation - Lingxu Kong; Huajie Yang; Jing Yang; Liujiangshan Jiang; Bin Xu; Tianyao Yang; Wei Liu (Ecotoxicology and Environmental Safety)
Methylmercury (MeHg) is a potent neurotoxicant with neurodevelopmental toxicity that is widely ingested into the body through drinking water and food. MeHg crosses the placental barrier and accumulates in the brain of the fetus, affecting the growth and development of the central nervous system. Although it has been demonstrated that MeHg induces neuronal calcium overload in the rat cerebral cortex, the role of calcium overload in MeHg-induced neurodevelopmental toxicity remains unclear. Here, we used ICR-pregnant mice and their resulting offspring and administered the BAPTA-AM calcium antagonist to investigate the molecular mechanisms by which MeHg exposure during gestation and lactation affects neurodevelopment. We found that exposure to MeHg during gestation and lactation resulted in developmental arrest and neurobehavioral dysfunction in the offspring, with calcium overload, disturbed mitochondrial dynamics, and apoptosis. However, the calcium overload inhibitor BAPTA-AM rescued MeHg-induced neurodevelopmental damage, attenuated the onset of calcium overload, reduced mitochondrial kinetic disturbances and apoptosis. Meanwhile, the activation of the CaM/CaMKII/DRP1 signaling pathway induced by calcium overload was inhibited, and the interaction between DRP1 and BAX was attenuated, which alleviated apoptosis to a certain extent. In summary, our study suggests that MeHg-induced calcium overload may induce disturbed mitochondrial dynamics through activation of the CaM/CaMKII/DRP1 signaling pathway, resulting in neuronal apoptosis.